PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN ENERGI DI BEI : PENDEKATAN MODEL GROVER - Celline Yulia Isabella; Lenni Yovita; Herry Subagyo; Bara Zaretta (MANAJEMEN, 2025)
Financial distress is a condition in which a company experiences financial decline prior to bankruptcy. Identifying financial distress is crucial for investors to anticipate the risk of bankruptcy. This study aims to examine the effect of financial distress on financial ratios, specifically liquidity ratio, profitability ratio, and leverage ratio. The population consists of all energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Purposive sampling was used as the sampling technique, resulting in a total of 340 research samples. The dependent variable is measured on a nominal scale, categorized as 0 for non-financial distress issuers and 1 for financial distress issuers. Data analysis was conducted using descriptive statistics, multicollinearity tests, data quality assessments, hypothesis testing, and logistic regression analysis with IBM SPSS version 25 software. The results indicate that the Current Ratio has a significant negative effect on financial distress. Similarly, the Net Profit Margin also has a significant negative effect on financial distress. Meanwhile, the Debt to Equity Ratio has a significant positive effect on financial distress.